2020
DOI: 10.21203/rs.2.17869/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adoption Rates of Electronic Health Records in Turkish Hospitals and the Relation with Hospital Sizes

Abstract: Background: Nation-wide adoption of electronic health records (EHRs) in hospitals has become a Turkish policy priority in recognition of their benefits in maintaining the overall quality of clinical care. The electronic medical record maturity model (EMRAM) is a widely used survey tool developed by the Healthcare Information and Management Systems Society (HIMSS) to measure the rate of adoption of EHR functions in a hospital or a secondary care setting. Turkey completed many standardizations and infrastructura… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Furthermore, it has been found that at least 60% of hospitals between the United States, Europe, and Asia still have a basic EMR system, 62 where a majority are classified as stages 0 to 2 according to the Healthcare Information and Management Systems Society’s Electronic Medical Record Adoption Model. The fact that our system stemmed from a basic HIS itself (stage 1) renders its results promising for hospitals with basic HIS and limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that at least 60% of hospitals between the United States, Europe, and Asia still have a basic EMR system, 62 where a majority are classified as stages 0 to 2 according to the Healthcare Information and Management Systems Society’s Electronic Medical Record Adoption Model. The fact that our system stemmed from a basic HIS itself (stage 1) renders its results promising for hospitals with basic HIS and limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we measured patient rating of the overall quality of care by using a single question using a 5-point Likert scale (1 = excellent, 2 = very good, 3 = good, 4 = fair, 5 = poor). Finally, we included patient demographics such as age group, gender, and race, and hospital characteristics such as hospital location (based on United States Census Bureau's urban and rural definitions of urban or rural) (25), size (small: 0–99 beds, medium: 100–399 beds, large: 400+ beds) (26,27), and teaching status (yes/no). A teaching hospital, also known as an academic medical center, partners with medical and/or nursing schools, education programs, and research centers to improve health care delivery through learning and research (28).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, automated versions of such track-and-trigger systems cannot be effectively implemented in hospitals with basic EMRs (i.e., staged as 0, 1, or 2 according to the Healthcare Information and Management Systems Society Electronic Medical Record Adoption Model adoption model classification 10 ), because they do not include an electronic nursing flowsheet documentation module. It is to be noted that the proportion of hospital with such basic EMRs is significant worldwide, especially in third-world countries 11 …”
mentioning
confidence: 99%
“…It is to be noted that the proportion of hospital with such basic EMRs is significant worldwide, especially in third-world countries. 11 A new and promising approach described in recent studies [12][13][14][15][16] involves the addition of physiological biomarkers measurements to the traditionally measured vital signs and demographic patient data routinely available in the EMR. Biomarkers are defined as biological characteristics (such as, e.g., the C-reactive protein (CRP), procalcitonin, serum creatinine, etc) that are objectively measured and used as indicators of certain physiopathological processes.…”
mentioning
confidence: 99%